Derivative Spectrophotometric Methods for the Determination of Bendamustine Hydrochloride - M. Mathrusri Annapurna,S. Pavani,S. Anusha,and Harika Mahanti (Journal of Applied Pharmaceutical Science)
Bendamustine hydrochloride is used to treat chronic lymphocytic leukemia. It kills the existing cancer cells and limits the growth of new cancer cells. Three simple, rapid and sensitive spectrophotometric methods were developed for the determination of Bendamustine hydrochloride in phosphate buffer (pH 8.0) (Method A) and boric buffer (pH 9.0) (Method B). Method C is a difference spectroscopy technique in which the amplitude was chosen for the analytical calculations. Bendamustine hydrochloride obeys Beer-Lambert’s law over the concentration range 1-40 µg/ml, 0.1-40 µg/ml and 5-40 μg/ml with regression equations y = 0.003x + 0.001(r² = 0.998) y = 0.0027x + 0.0005 (r² = 0.999), and y = 0.0034x + 0.006 (r² = 0.994) for Method A, B and C respectively. The methods were validated as per ICH guidelines and can be applied for the determination of Bendamustine hydrochloride in pharmaceutical formulations.
Keywords: Bendamustine hydrochloride,Derivative spectroscopy,Difference spectroscopy,Validation.